APLIKASI KAMUS INGGRIS – INDONESIA DENGAN FITUR SPEECH TO TEXT - Rima Anggraini; Danuri Danuri; Agus Tedyyana (Infotekmesin, 2018)
the use of dictionaries is not only used manually by searching for words in the dictionary book but also digitally which facilitates the work in searching for the meaning of the word. Due to the number of dictionary applications at this time it is done in the development of dictionary applications supported speech to text features in the search he said. Making this application using SQLite database and editor of Android Studio. The use of this dictionary not only functions in searching for the meaning of words, but there is also a list of tensis that comes with text to speech. This application can make it easier to find words and know about tensis. The end result of this application has been tested with several smarthphone with different android version and the result of this application can run well. The drawback of this application is the use of speech to text features that are still online, and data that can be entered into SQLite can not be much and limited, text to speech can not explain tensis accurately.